PENGHENTIAN PENUNTUTAN BERDASARKAN KEADILAN RESTORATIF DI KEJAKSAAN NEGERI JAKARTA TIMUR - Fadli Hadiputro (2022)
The Prosecutor's Office of the Republic of Indonesia in 2020 issued a legal umbrella regarding the application of restorative justice in the criminal justice system in Indonesia through the Regulation of the Prosecutor's Office of the Republic of Indonesia (Perja) Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. With the implementation of Perja Number 15 of 2020 at the prosecution level, the Public Prosecutor can stop prosecutions based on restorative justice, so that the cases handled do not need to be transferred to court. This is what motivated the author to conduct research to discuss the normative provisions for stopping prosecution based on restorative justice as regulated in Perja Number 15 of 2020 (Law in the book) and its application in the field, namely at the East Jakarta District Attorney (Law in action). The method used in this research is Juridical Empirical which is carried out through field research by seeing and observing what is happening in the field, the application of these regulations in practice in society. While the data used are primary data and secondary data. The results of the study concluded, firstly, Perja Number 15 of 2020 regulates the requirements of a case whether or not a prosecution can be terminated based on restorative justice by considering aspects of human values, law, and justice that live in society. Second, the implementation of the termination of prosecution of general criminal cases at the East Jakarta District Attorney has been in accordance with Perja No. 15 of 2020. Public prosecutors at the East Jakarta District Attorney's Office in determining whether or not cases can be transferred to the court have considered aspects of human, legal, and ethical values. justice that lives in society, rather than imposing sanctions in order to create laws that are just, certain and useful.Keywords: Prosecutor's Office, Termination of Prosecution, Restorative Justice Keywords: Prosecutor's Office, Termination of Prosecution, Restorative Justice